FAKTOR YANG BERHUBUNGAN DENGAN KADAR HEMOGLOBIN PADA PETUGAS STASIUN PENGISIAN BAHAN BAKAR UMUM (SPBU) DI KECAMATAN JAMBI SELATAN KOTA JAMBI - Rizki Eggy Aprilian S; T Samsul Hilal; Novi Berliana (Jurnal Inovasi Penelitian, 2023)
The use of fuels such as premium and diesel releases 95% of lead emissions that can pollute the air and can then be inhaled and absorbed by the body so that it can cause health problems such as decreased hemoglobin levels which can interfere with the hematological system because it interferes with the formation of red blood cells (erythropoesis) by inhibiting protoporphyrin synthesis and interfering with iron absorption so that it can increase the risk of high anemia. This study is a quantitative study with a cross sectional design. The research sample was public filling station officers who refueled as many as 46 people. The research instruments were questionnaires and easytouch brand digital hemometers. Data were analyzed univariately and bivariately using the chi square statistical test. The results showed that 60.9% of respondents had normal hemoglobin levels, 52.2% of respondents were > 30 years old, 67.4% of respondents were male, 63.0% of respondents used personal protective equipment and 52.2% of respondents had a new working period. The results of bivariate analysis showed there was a relationship between the use of personal protective equipment (0.016) and tenure (p=0.019) with hemoglobin levels in public fuel station officers in South Jambi District. There is no relationship between age (p=0.503) and gender (p=1.000) with hemoglobin levels in public refueling station officers in South Jambi District.